Rowing ergometer kinematics of collegiate female rowers - LeMunyon, C.; Carlson, K. (Topics in Exercise Science and Kinesiology, 2020)
The purpose was to quantify rowing kinematics of female rowers and compare how rowing mechanics concurred with the rowing style taught by the coaching staff. Rowing kinematics at various paces were captured using Xsens motion capture hardware and processing software. Point of application 1: Lack of knee extension at the end of the drive phase limited the knee range of motion and time for force development. Point of application 2: Elbow flexion and hip extension occurred too early in the stroke leading to poor skeletal segmental interactions. Point of application 3: It was determined that the rowers examined in this study did not use the Rosenberg style fully.